2018
DOI: 10.1002/ep.13087
|View full text |Cite
|
Sign up to set email alerts
|

Impact of changing environmental factors and species competition on iron filings‐based green environmental media for nutrient removal in stormwater treatment

Abstract: Iron filings‐based green environmental media (IFGEM) is a new type of green sorption media that may be applied to heterogeneous environments for removing nutrients. To confirm the reliability and efficacy of this new green sorption media, multiple factors must be considered for a holistic assessment, primarily temperature effect, varying influent concentration, changing pH value, varying iron filing content, presence of iron filings, and interaction (competition) between nutrient species such as nitrogen and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Phosphorus is removed by plants and microbial uptake or absorbed by the filter media (Marvin et al, 2020). Many studies focused on the efficacy and the mechanism involved in nitrogen (Jiang et al, 2017;Tian et al, 2019;Wu et al, 2017) and phosphorus (Chang et al, 2019;Zhang et al, 2018a) removal, but few studies have examined the long-term performance in SBS (Table 2). Previous research suggested that SBS could reduce nutrients after a long-term operation.…”
Section: Nutrientsmentioning
confidence: 99%
“…Phosphorus is removed by plants and microbial uptake or absorbed by the filter media (Marvin et al, 2020). Many studies focused on the efficacy and the mechanism involved in nitrogen (Jiang et al, 2017;Tian et al, 2019;Wu et al, 2017) and phosphorus (Chang et al, 2019;Zhang et al, 2018a) removal, but few studies have examined the long-term performance in SBS (Table 2). Previous research suggested that SBS could reduce nutrients after a long-term operation.…”
Section: Nutrientsmentioning
confidence: 99%
“…Iron filings as an additive to bioretention media were shown to improve the removal of N and P in a bioretention column study (Chang, Wen, & Wanielista, 2019). Combinations of sand with a 3.8% and a 5% content iron filing mix (v/v) were compared with a natural soil control.…”
Section: Annual Literature Reviewmentioning
confidence: 99%
“…In addition to regulating K s , different amendments were used in bioretention media to improve its water purification ability. Studies showed that amendments such as blast furnace slag, biochar, water treatment residuals (WTRs), and iron filings could improve the total phosphorus (TP) and total nitrogen (TN) removal ability of the bioretention media (Li et al, 2016;Chang et al, 2019;Poor et al, 2019;Zhou et al, 2022).…”
Section: Introductionmentioning
confidence: 99%